STATUS UJRAH (UPAH) PADA AKAD IJARAH: STUDI UPAH FOTOGRAFER PRE WEDDING - Tiana, Selvi; Ngatiyar, Ngatiyar (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2022)
The purpose of this study is to explain the position of ujrah or wages generated in the work of pre-wedding photographers which are thought to cause several problems. As a photographer, he plays a role in taking pre-wedding photos which are done with various poses or different styles, such as the style of being alone, hugging, touching each other and even revealing their genitals. The research method used is qualitative research with literature (library research), namely a series of activities relating to the methods of collecting library data, reading and recording and processing research materials. library research only utilizes library resources to obtain research data and limits its activities to library materials without requiring field research. The results showed that the ujrah (wages) resulting from taking pre-wedding photos were considered doubtful or unclear. Because in the implementation process there are elements that are not in accordance with the rules of Islamic law.